1975
DOI: 10.1007/bf00614010
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and pharmacokinetics of sulfinpyrazone (Anturan�) in man

Abstract: The absorption, biotransformation and elimination of sulfinpyrazone, 1,2-diphenyl-3,5-dioxo-4-(2'-phenylsufinylethyl)-pyrazolidine, have been studied by administration of single 200 mg oral doses of a 14C-labelled preparation to two male volunteers. Absorption from the gastro-intestinal tract was rapid and complete and the plasma concentration of unchanged drug reached maximum values of 22.67 and 13.04 mug/ml, respectively, after 1 - 2 hours. The elimination half-life in the two subjects, calculated from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…It has been reported previously that phenylbutazone and sulfinpyrazone, which are both C-glucuronidated in humans (Dieterle et al, 1975;Aarbakke, 1978), inhibit the glucuronidation of AZT in vitro (Resetar et al, 1991;Rajaonarison et al, 1992). The present study confirmed that phenylbutazone and sulfinpyrazone inhibited UGT2B7, the enzyme responsible for AZT glucuronidation.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported previously that phenylbutazone and sulfinpyrazone, which are both C-glucuronidated in humans (Dieterle et al, 1975;Aarbakke, 1978), inhibit the glucuronidation of AZT in vitro (Resetar et al, 1991;Rajaonarison et al, 1992). The present study confirmed that phenylbutazone and sulfinpyrazone inhibited UGT2B7, the enzyme responsible for AZT glucuronidation.…”
Section: Discussionmentioning
confidence: 91%
“…This metabolite was reported to be a major metabolite in humans (Dieterle et al, 1980). A secondary C-glucuronide metabolite of sulfinpyrazone, i.e., a metabolite of its sulfone metabolite, has also been reported (Dieterle et al, 1975). Studies have shown that recombinant human UGT1A9 catalyzed the formation of sulfinpyrazone-Cglucuronide in vitro (Kerdpin et al, 2006).…”
Section: Carbon-linked Glucuronidesmentioning
confidence: 99%
“…Methods Fifty-eight apparently healthy male mongrel dogs that weighed [22][23][24][25][26][27][28][29][30][31][32] kg were used for the study. After an 18-hour period of fasting, all dogs on the day of the experiment were anesthetized with morphine sulfate (3 mg/kg i.m.)…”
mentioning
confidence: 99%